Peran Guru BK dalam Meningkatkan Penyesuaian Diri Siswa Baru di MTS Al-Jami’yatul Washliyah Tembung - Sekar Lestari; Ali Daud Hasibuan (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
Guidance and counseling teachers have an important role regarding the ability to adapt to students. The purpose of this research is to describe the role of the counseling teacher in improving students' adaptability. Qualitative approach is the method used for this research. Data was collected through a process of observation (observation), documentation and interviews at MTs Al Jam'iyatul Washliyah Tembung. The resulting data were analyzed using Milles and Huberman's theory, namely the existing data was reduced and then presented into a pattern, drawing a conclusion and verifying the resulting data. This research resulted in a finding that the counseling teacher plays an important role in improving the ability to adapt to new students, namely as a provider of information, activity organizer, motivational provider and giving direction. Another method used by the counseling teacher is asking students to make adjustments to the teacher and adjustments to friends.